The Australian genus Rhytiphora (Coleoptera: Cerambycidae: Lamiinae) with a revision of the Rhytiphora collaris group - Ashman, Lauren G.; Keyzer, Roger De; Ślipiński Adam (Zootaxa, 2023)
We present a review of the Australian species of Rhytiphora Audinet-Serville, 1835, the most speciose longhorn beetle (Cerambycidae) genus in Australia. The morphological definition of the genus is updated, including useful features to distinguish Rhytiphora from closely related genera within Niphonini. Key characteristics of the two molecularly determined subclades are also provided. The collaris group of Rhytiphora is revised and Rhytiphora garnetensis sp. nov. is described from Queensland. A neotype is designated for Saperda collaris Donovan, 1805; lectotypes are designated for R. amicula White, 1859, Symphyletes vestigialis Pascoe, 1864, Symphyletes compos Blackburn, 1902, R. maculosella Blackburn, 1902, R. uniformis Blackburn, 1901, R. piperitia Hope, 1842 and Symphyletes humeralis White, 1858. A number of species complexes that require genetic confirmation before being synonymised (or separated) are discussed. Finally, we provide a new checklist of the Australian Rhytiphora species which, incorporating synonymies and other changes, reduces the total number of species from 206 to 163. The following species have been synonymised (junior synonym listed first): Coptops abdominalis White, 1858 (= Lamia bankii Fabricius, 1775); Penthea adamsae McKeown, 1938 (= Penthea macularia Pascoe, 1867); R. affinis Breuning, 1970 (= Symphyletes farinosus Pascoe, 1863); Prosoplus albidus Aurivillius, 1917 and Prosoplus minimus Breuning, 1938 (= Corrhenes pauxilla Blackburn, 1901); Prosoplus albostriatus Breuning, 1938 and Prosoplus demarzi Breuning, 1963 (= Niphona oblita Pascoe, 1863); Saperda albocincta Guérin-Méneville, 1831, Symphyletes compos Blackburn, 1902, R. donovani Newman, 1851, R. intertincta Pascoe, 1867, R. maculosella Blackburn, 1902, R. parafarinosa Breuning, 1970, R. vermiculosa Breuning, 1970 and Symphyletes vestigialis Pascoe, 1864 (= Saperda collaris); R. albolateraloides Breuning, 1970 (= Platyomopsis cinerascens Aurivillius, 1917); Symphyletes anaglyptus Pascoe, 1867, Saperdopsis armata Thomson, 1864, Symphyletes moratus Pascoe, 1863 and Symphyletes vetustus Pascoe, 1862 (= Lamia pulverulens Boisduval, 1835); Symphyletes arctos Pascoe, 1865 (= Symphyletes fumatus Pascoe, 1864); Pterolophia australica Breuning, 1938 (= Apomecyna nigrita Pascoe, 1859); R. barnardi Breuning, 1982 (= Symphyletes capreolus Pascoe, 1867); Platyomopsis basalis Aurivillius, 1917 (= Saperdopsis ochreobasalis Breuning, 1938); R. corrhenoides Breuning, 1970 (= Corrhenes cruciata Pascoe, 1875); R. dawsoni Breuning, 1970 (= Symphyletes fasciatus Blackburn, 1901); Symphyletes defloratus Pascoe, 1869 (= Symphyletes gallus Pascoe, 1864); Trichoprosoplus demarzi Breuning, 1961 and Paradaxata spinosa Breuning, 1938 (= Paradaxata villosa Breuning, 1938); Prosoplus elongatus Breuning, 1938 (= Prosoplus metallescens Breuning, 1938); Corrhenes flavovittata Breuning, 1938, Saperda funesta Pascoe, 1859, Anaesthetis lepida Germar, 1848 and Cobria rufa Breuning, 1961 (= Saperda paulla Germar, 1848); Corrhenes guttulata Pascoe, 1865, Corrhenes macmillani Gilmour, 1950 and Saperda mystica Pascoe, 1863 (= Saperda stigmatica Pascoe, 1863); Xiphotheopsis hathlioides Breuning, 1961 (= Xiphohathlia lobata Breuning, 1961); Symphyletes iliacus Pascoe, 1866 (= Symphyletes deserti Blackburn, 1896); Saperdopsis laterialba Breuning, 1938 (= Symphyletes satelles Pascoe, 1865); Etaxalus laterialbus Breuning, 1968 (= Achriotypa basalis Pascoe, 1875); Prosoplus laterinigricollis Breuning, 1961 and Prosoplus mediofasciatus Breuning, 1938 (= Niphona bakewelli Pascoe, 1859); R. leucolateralis Breuning, 1970 (= R. subargentata Breuning, 1970); Penthea lichenosa McKeown, 1942 and Penthea obscura Breuning, 1961 (= Penthea scenica Pascoe, 1863); Sysspilotus macleayi Pascoe, 1865 and Menyllus maculicornis Pascoe, 1864 (= Menyllus rotundipennis Breuning, 1968); R. multituberculata Breuning, 1966 (= Saperdopsis sellata Breuning, 1938); Symphyletes nodosus Newman, 1842 (= Acanthocinus piliger Macleay, 1826); Hathliodes pseudomurinus Breuning, 1938 (= Hathliodes virgatus Breuning, 1938); Penthea sectator Pascoe, 1865 (= Penthea crassicollis Pascoe, 1864); R. simsoni Blackburn, 1901 (= R. mista Newman, 1842); Penthea solida Pascoe, 1863 (= Lamia vermicularia Donovan, 1805); Platyomopsis spinosa Thomson, 1864 (= Lamia obliqua Donovan, 1805); R. truncata Breuning, 1940 (= R. piperitia Hope, 1842); R. uniformis Blackburn, 1901 (= Platyomopsis delicatula McKeown, 1948); Mimiphiastus vivesi Breuning, 1978 (= Symphyletes variolosa Pascoe, 1862). Pterolophia bispinosa Breuning, 1938 is renamed to R. subovata new name (junior homonym of Saperdopsis bispinosa Breuning, 1938), R. browni McKeown, 1938 is reinstated as its own species, and Corrhenes flavovittata demarzi Breuning, 1963 is elevated to species status and renamed R. rentzi new name (junior homonym of Trichoprosoplus demarzi).